Graphene Oxides Coated Paper as a Substrate to Paper Spray Ionization Mass Spectrometry for Creatinine Determination in Urine Samples - Fernandes,Aline R. (2019)
Paper spray ionization (PSI) is a promising analytical tool for direct analysis in mass spectrometry (MS). However, this technique usually uses chromatographic paper, which rarely accomplishes a stable MS signal and could vary with the sample matrix effect. In the present study, the application of graphene oxides (GO) was scrutinized as modifier paper substrate for PSI-MS methods. The developed substrate efficiency was evaluated towards creatinine determination in urine samples. The GO-PSI-MS developed method for creatinine in urine samples showed linearity in the range of 0.1 to 3.4 ppm with R2 = 0.9991. The precision was evaluated and the values were between 1.1 to 6.8% and the accuracy above 96.8%. The limit of quantification (LOQ) and limit of detection (LOD) were 0.05 and 0.17 ppm, respectively. The GO-PSI developed was compared to conventional chromatographic paper for PSI-MS methods, and the results showed that the modified paper with GO bolsters method linearity, precision, and LOQ values.